2022
DOI: 10.1038/s41586-022-05154-6
|View full text |Cite
|
Sign up to set email alerts
|

African-specific molecular taxonomy of prostate cancer

Abstract: Prostate cancer is characterized by considerable geo-ethnic disparity. African ancestry is a significant risk factor, with mortality rates across sub-Saharan Africa of 2.7-fold higher than global averages1. The contributing genetic and non-genetic factors, and associated mutational processes, are unknown2,3. Here, through whole-genome sequencing of treatment-naive prostate cancer samples from 183 ancestrally (African versus European) and globally distinct patients, we generate a large cancer genomics resource … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 50 publications
9
73
0
Order By: Relevance
“…33,34 While limited in sample size, our study suggests that rare fusion events beyond TMPRSS2-ERG may drive PCa in men of Nigerian ancestry. A recent study by Jaratlerdsiri et al 35 showed that PCa…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…33,34 While limited in sample size, our study suggests that rare fusion events beyond TMPRSS2-ERG may drive PCa in men of Nigerian ancestry. A recent study by Jaratlerdsiri et al 35 showed that PCa…”
Section: Discussionmentioning
confidence: 98%
“…While limited in sample size, our study suggests that rare fusion events beyond TMPRSS2‐ERG may drive PCa in men of Nigerian ancestry. A recent study by Jaratlerdsiri et al 35 showed that PCa samples from men of African ancestry have high genomic mutational burden and have more genomic heterogeneity compared to samples from European ancestry. In our study, the detection of rare fusion events in Nigerian PCa may suggest a potentially high level of gene‐rearrangement heterogeneity within Nigerian PCa patients compared to European patients, though we lack representative transcriptomic profiles for Nigerian PCa patients of African ancestry from the African continent.…”
Section: Discussionmentioning
confidence: 99%
“…On 31 August 2022, we published two papers simultaneously in Nature and Genome Medicine, aimed at providing a first glimpse into the genomic contribution to PCa health disparity for men from Sub‐Saharan Africa. 3 , 4 Generating deep sequenced blood and matched tumour genome data for 183 largely treatment naïve and clinicopathologically aggressive disease‐presenting patients, besides 53 Australians and seven Brazilians, the study included 123 South Africans. Through ancestral interrogation of inherited variation, patients were further genetically classified as African ( n = 113; all South African), European ( n = 61; 53 Australian, five South African, and three Brazilian) or Admixed ( n = 9; five South African and four Brazilian).…”
Section: Tablementioning
confidence: 99%
“…Prostate cancer (PCa) is one of the most prevalent diagnosed malignancies affecting men worldwide, with increasing cancer-related mortality [43][44][45] . Currently, the widely used serum prostate-specific antigen (PSA) screening lacks sufficient specificity and sensitivity for clinical diagnosis of PCa.…”
Section: Dynamic Monitoring Of Dual-surface-protein-guided Liposome P...mentioning
confidence: 99%